(untitled) (Orinoquia, 2011)
Titulo en ingles: Designing an electronic identification system and its potential use inbeeftraceability RESUMEN: Se diseñó un sistema de identificación electrónica para ganado y su potencial uso en la trazabilidad de la carne bovina. Se utilizó la tecnología RFID, junto con un sistema de información orientado a web donde se involucraron los diferentes actores de la cadena cárnica. El dispositivo lector RFID fue probado y funcionó bajo condiciones reales, obteniendo lecturas correctas a una distancia de la piel del animal entre 5-10 cm, aunque presentó limitaciones en la ergonomía podrían ser mejoradas, permitiendo una mayor facilidad de uso. Palabras Clave: RFID, bovinos, identificación. ABSTRACT: An electronic identification (EID) system was designed for livestock and its potential use in beef traceabil- ity was considered. Radio-frequency identification (RFID) technology was used, along with a web-orien- tated information system involving the different actors in the meat chain. The RFID reader device was tested and operated in real conditions, accurate readings beingobtainedat a 5-10 cm distance from an animal’s skin. Although there were some limitations regarding the ergonomics involved in its use, the secould be improved, allowing itsgreater ease of use. Key words: Radio-frequency identification (RFID), bovine, electronic identification (EID)